2021
DOI: 10.1108/joic-12-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of compliance audit on companies’ compliance with disclosure guidelines of financial statements

Abstract: Purpose This paper examines the relevance of compliance audit on companies’ compliance with disclosure guidelines of financial statements with special reference to the case of companies registered in the Muscat Securities Market (MSM), Oman. Design/methodology/approach This paper adopts a direct measure of compliance prescribed and published in the annual report of Capital Market Authority (CMA) and its executive regulation from period 2011 to 2019. Findings The finding shows that there is a positive assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…As CSR is a growing concern, it is believed that some critic's view on CSR is largely ineffective in perception as a negative influence of business on society and leads to scarcity of public goods (Schneider, 2020). CSR compliance with stakeholder's profitability targets is often in disagreement with the cost engaged input up CSR practices (Sahut et al ., 2019; Thottoli, 2021a). Some of the countries made CSR spending and disclosures as mandatory requirements.…”
Section: Introductionmentioning
confidence: 99%
“…As CSR is a growing concern, it is believed that some critic's view on CSR is largely ineffective in perception as a negative influence of business on society and leads to scarcity of public goods (Schneider, 2020). CSR compliance with stakeholder's profitability targets is often in disagreement with the cost engaged input up CSR practices (Sahut et al ., 2019; Thottoli, 2021a). Some of the countries made CSR spending and disclosures as mandatory requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative strategies for corporate branding should be employed by hotel industries by applying the latest information communication technology tools in connection with marketing on corporate branding, compliance with internal regulations on corporate branding, accounting on corporate branding and auditing on corporate branding to enhance the firm’s financial performance (Thottoli, 2021c, d; Thottoli, Thomas, & Ahmed, 2019a, b, c; Thottoli & Thomas, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the field of a compliance audit is still in its early stages of development. Although there have not been any past studies that have examined all the compliance audit research disciplines, as indicated by [5], the exponential rise in publications testifies to the growing interest in this field of study. Furthermore, no previous articles have offered a bibliometric study with comprehensive coding analysis based on the supporting evidence, goals, and potential research prospects.…”
Section: Discussionmentioning
confidence: 99%
“…However, they fail to comply with business regulations and are penalized severely by the government. However, a compliance audit and sustainability accounting reports guarantee improved oversight of the organization's legal issues and help to abide by a variety of additional rules, including tax laws, environmental laws, consumer protection laws, and other related business laws [4][5][6] aimed to test how stakeholders are involved in the sustainability accounting and reporting processes of Australian local councils.…”
Section: Introductionmentioning
confidence: 99%